To give or not to give, and to whom?—These are the questions! Determinants of selective organ donation intentions - Cobzeanu, Alexandra; Opariuc-Dan, Cristian; Merlici, Ioan-Alex; Cobzeanu, Bogdan Mihail; Tanase, Ionut (Frontiers in Psychology, 2025)
IntroductionThis study examined the psychological factors influencing intentions for Posthumous Organ Donation (POD). Specifically, we focused on beliefs associated with POD, perceived subjective and moral norms derived from the extended Theory of Planned Behavior, empathic concern, and a facet of utilitarianism, namely instrumental harm. We explored these variables in relation to participants' overall intention to donate organs, as well as their intention to donate in specific contexts: to a child and to an adult with disabilities.MethodsA total of 1,896 Romanian adults aged 18 to 80 participated in the study. Data were analyzed using a moderated structural equation modeling approach to assess the role of medical mistrust, disgust-related factors (Ick and Jynx), bodily integrity concerns, perceived benefits, norms, empathic concern, and instrumental harm in predicting POD intentions.ResultsMedical mistrust, Ick, Jynx, and bodily integrity concerns had significant negative effects on POD intentions. In contrast, perceived benefits, as well as subjective and moral norms, positively predicted POD. Empathic concern did not significantly moderate POD intentions. However, instrumental harm was negatively associated with all forms of POD (general, to a child, and to an adult with disabilities). Participants reported the highest POD intentions when the recipient was a child with disabilities, and the lowest intentions for general POD.DiscussionThe findings suggest that while normative beliefs and perceived benefits enhance willingness to engage in POD, concerns about bodily integrity, mistrust, and aversion responses hinder such intentions. The role of instrumental harm underscores the ethical complexities in organ donation decision-making. Context also matters, as donation to vulnerable recipients (e.g., children with disabilities) elicited the strongest support. These results highlight the importance of addressing mistrust and disgust-related barriers, while strengthening moral and normative frameworks, to promote organ donation.